Characterization and modeling of poly(methyl methacrylate) and thermoplastic polyurethane for the application in laminated setups. (October 2017) - Rühl, Andreas; Kolling, Stefan; Schneider, Jens
Highlights: The article shows the transferability of DMTA result to model the uniaxial tensile behavior poly(methyl methacrylate) (PMMA) with standard viscoelastic models. A unique investigation using synchronized DIC and IR surveillance regarding the thermos-mechanical behavior of TPU was performed showing a significant temperature rise of the material. The article contributes to the standardization of experiments and modeling of PMMA and TPU and related materials with special regards to their application in laminates. Abstract: Transparent polymeric laminates are increasingly used for the substitution of conventional glass and laminated safety glass respectively and thus require reliable and efficient prediction and modeling techniques, in particular for numerical simulations. In the present work, the components of a polymeric laminate consisting of poly(methyl methacrylate) (PMMA) plies combined with a thermoplastic polyurethane (TPU) interlayer were subjected to experimental and numerical investigation. Uniaxial tensile tests and dynamic mechanical thermal analysis (DMTA) were used to determine the strain-rate and temperature dependent material behavior. Adiabatic heating of the interlayer was observed using infrared (IR) surveillance. Based on the experimental basis, viscoelastic material models were applied for both materials. The corresponding parameter identification was performed in two ways. One was based on the DMTA master curve, the other on uniaxial tensile test data. The material models were able to capture the temperature and time dependent behavior of both materials adequately and enable their usage in a laminated structure.